A model for prioritizing outsourceable activities in universities through an integrated fuzzy-MCDM method. Issue 5 (15th April 2022) - Kiani, Mehrdad; Bagheri, Moslem; Ebrahimi, Abolghasem; Alimohammadlou, Moslem
Abstract: This study investigated outsourceable activities through fuzzy multi-criteria decision-making (FMCDM) techniques. The study, which involved five phases, relied on an integrated, exploratory research method. In phase 1, the qualitative method of meta-synthesis was used to identify the factors effecting outsourcing decisions. Next, the Delphi method was employed; in phase 3, questionnaires including paired comparisons of the items were submitted to 12 experts and the data gathered were analyzed through fuzzy analytical hierarchy process (FAHP). The importance rate of every criterion was then decided. In phase 4, following an investigation into the available documents and identification of nine outsourceable activities at an Iranian university, the data for analysis were collected through the questionnaires submitted to 12 experts. The data were then prioritized through fuzzy SAW, fuzzy TOPSIS and fuzzy VIKOR. Finally, given the fact that the results of these methods were conflicting, aggregate techniques, namely rank average, Borda and Copeland, were used to reach a consensus. As the findings revealed, the Medical Sector and Installation Affairs Department of the Sciences College and of the Humanities College showed the top ranks, followed by the Computer Affairs Department of the Sciences College and of the Humanities College, and the Veterinary Clinic, respectively. The study proposed a model for ranking outsourceable activities, suggesting that decision-makers and researchers would have to consider numerous criteria and several methods simultaneously for selecting outsourceable activities.